Hubungan antara Religiusitas dan Pendidikan Karakter di Rumah terhadap Akhlak Siswa di Madrasah Tsanawiyah Negeri Surakarta - Ummah, Nisaul Khoiru; Khuriyah, Khuriyah (Center of Language and Cultural Studies, 2021)
This research aims to see the relationship between religiosity and morals, character education at home and morals, and religiosity and character education at home to the morals of students at Mts Negeri 2 Surakarta. This research uses the correlational method conducted from March 2020 to August 2020. Assigning 81 samples, this research selected at random, this research used a questionnaire to collect data. Data were tested using inferential statistics with the help of SPSS Release 23.0. Hypothesis testing was analyzed using multiple correlation analysis tests. Prior to the analysis, classical assumption tests to see the normality, linearity, multicollinearity, and heteroscedasticity were done. Results show 1) religiosity and student morals exists significantly with a sig (2-tailed) at 0.000 (p=0.000 <0.05). It means there is a significant relationship between religiosity and student morals. 2) character education at home and the morals of students exists with a sig value (2-tailed) at 0.000 (p=0.000 <0.05), meaning there is a significant relationship between character education at home and student morals 3) religiosity and education character at home towards student morals exists partially and simultaneously. As the F Change value is 0.000 which means <0.05, the study concludes that religiosity and character education at home have a significant correlation to student morals.